Learning from Bernardino Ramazzini, a tribute to the Magister from Carpi and to the Fellows of the Collegium Ramazzini - Grandjean, Philippe (European Journal of Oncology and Environmental Health, 2016)
Bernardino Ramazzini became famous as the author of the first textbook on occupational medicine, but his lasting importance to medicine and public health also includes his logical approach to medical diagnosis and prevention. While relying on background evidence, he explored the patient’s environment and learned from the victim before recommending preventive intervention. This approach was later adopted by Irving J. Selikoff, and it has helped gaining insight into modern impacts of environmental pollution. A prime example is mercury, a hazard that already Ramazzini examined. Recent experience on this pollutant has disclosed that epidemiological findings easily underestimate the extent of exposure-related adverse effects. In their publications, scientists often use hedged language that may be misunderstood and misused, especially by vested interests. Mounting scientific evidence on mercury and other exposures has led to the recognition of the developmental origin of health and disease as an important paradigm that emphasizes the extreme vulnerability during early life-stages, where especially the developing brain is now known to be a key target organ for neurotoxicants, such as methylmercury. Had Bernardino Ramazzini been around today, he would have used his logical approach to focus on the health of the next generation.